Peningkatan Motivasi Belajar Peserta Didik melalui Model Pembelajaran Problem Based Learning (PBL) di Kelas VII SMP Negeri 2 Lolomatua Tahun Pelajaran 2022/2023 - Delfi Merdiana Halawa (Departement of Mathematics Education, 2024)
The objectives of this research are: (1) To describe the application of the Problem Based Learning Model in increasing motivation to learn mathematics regarding algebraic forms in class VII students at SMP Negeri 2 Lolomatua, Lolomatua District, South Nias Regency, Academic Year 2022/2023. (2) To determine the increase in motivation to learn mathematics in the form of Algebra after implementing the Problem Based Learning Model in class VII students at SMP Negeri 2 Lolomatua, Lolomatua District, South Nias Regency, Academic Year 2022/2023. The research uses the Kemmis design model based on cycles, consisting of four stages, namely action planning, implementation, observation and reflection. The research subjects were class VII of SMP Negeri 2 Lolomatua, Lolomatua District, South Nias Regency, Academic Year 2022/2023. With a class of 25 students and the instruments used in this research are documentation/RPP, observation and tests. The results obtained from research based on improvement observation data showed an increase in student learning motivation in the pre-cycle of (61.1) in the first cycle (68.4) students received motivation above the Learning Completeness Standard, in the second cycle it increased to (89.4 ) From the learning improvements carried out by researchers, it can be concluded that the use of the Problem Based Learning Model method increases learning motivation in the pre-cycle - 1st cycle learning with an increase of 7.3%. Meanwhile, learning cycle 1 - cycle 2 experienced an increase of 20.9%.